الامام عبد الوهاب الشعراني (ت973ه) وجهوده في الدعوة الى الله - شراحي, حياة; مصباحي, عفاف (University of Eloued-جامعة الوادي, 2022)
"تتناول هذه الدراسة جانبا من جهود الإمام عبد الوهاب الشعراني في الدعوة إلى الله-من خلال مؤلفاته المعروفة-كأحد أعلام القرن العاشر الهجري الذي تميز بأوضاعه الصعبة والفاسدة في أغلبها؛ حيث اعتمد الإمام الشعراني في مواجهة المخالفات الدينية والأخلاقية في عصره على زاويته ومؤلفاته ، ومن خلال إظهار نفسه كقدوة للناس، بروح التسامح والاحتواء والتفهم، نابذا الاختلاف السلبي داعيا إلى التقارب والوحدة؛ حيث شملت دعوته الإصلاحية في سبيل تكوين مجتمع مسلم صالح فعال مختلف الجوانب المعرفية منها والإيمانية والأخلاقية التربوية، سواء على مستوى الحكام أم المحكومين أم الصوفية أم العلماء، يتدرج فيها حسب الأهم فالمهم بما يتماشى ومستوى تفكير الناس آنذاك بأسلوب لين وسهل، فذاع صيته واشتهرت منهجه في الدعوة بما يجزم بحرصه على الإصلاح ونشر التدين السليم. وفي عصرنا الحالي الذي انهارت فيه الأخلاق وكثر فيه الخلاف بين المسلمين عامتهم وخاصتهم يحق لنا أن نستلهم من منهج الإمام الشعراني في الدعوة إلى الله ما يوحد صف المسلمين ويرشدهم نحو الطريق الصحيح للإسلام الذي كان عليه النبي صلى الله عليه وسلم وأصحابه .""This study deals with an aspect of the efforts of Imam Abdul-Wahhab Al-Shaarani in calling to God - through his various works - as one of the flags of the tenth century AH, who was distinguished by his difficult and mostly corrupt conditions; In facing the religious and moral violations of his time, Imam al-Shaarani relied on his school and writings, and by showing himself as a role model for people, in the spirit of tolerance, containment and understanding, rejecting negative differences and calling for rapprochement and unity; Where the reform call included - in order to form a righteous and effective Muslim society - the various aspects of knowledge, belief, and moral education, whether at the level of rulers or the ruled, Sufis or scholars. His approach to advocacy was well clear, which affirms his keenness on reform and spreading sound religiosity. In our current era, in which morals have collapsed and there is a lot of disagreement between Muslims, the common people and their private ones, we have the right to draw inspiration from the approach of Imam al-Sha’rani in calling to God what unites the Muslims’ ranks and guides them towards the correct path of Islam that the Prophet, may God’s prayers and peace be upon him and his companions, were upon."
مذكرة ماستر
Keywords: الامام عبد الوهاب الشعراني_القرن العاشر الهجري; Imam Abd al-Wahhab al-Shaarani - the tenth century AH